THE EFFECT OF USING KIDS SONG TO TEACH VOCABULARY TOWARD THE FIRST GRADE STUDENTS OF MTSN BANTAENG - Astri, Ahyani Astri; Said, Abdul Muis; Rauf, Masykur (elstic : english language linguistics culture, 2023)
This study aims to determine whether there is an effect of using kids' song in teaching vocabulary towards the first-grade students of MTsN Bantaeng. This research is experimental research that uses a quasi-experimental design and a non-equivalent control group. The population in this study was the first-grade of MTsN Bantaeng in the 2021/2022 academic year. The sample used was class VII A as the experimental class and class VII B as the control class. Data collection in this study used vocabulary test in the pre-test and post-test with a test form of fill in the blank. The instrument used is a multiple-choice test. The data obtained are analyzed using descriptive statistical analysis techniques and inferential statistics (t-test). The results of the study show that the average score of the vocabulary learning outcomes using kids' song is b 82.00. Then the average score of vocabulary learning outcomes that do not use kids' song (conventional method) is 75.50. Hypothesis testing using t-test shows t-count > t-table (t-count = 3.777 > t-table = 2.306). Based on the results of this study that there is a significant difference in the results of learning vocabulary using kids’ song which are higher than using conventional medium, so that it can be said that there is an effect of using kids’ song in teaching vocabulary to first graders of MTsN Bantaeng in the 2021/2022 school. The effect of kids’ song has proven that students feel happy, excited and easy to memorize vocabulary in learning English. This is really helps English teacher to be more inventive and imaginative in finding new methods for teaching vocabulary that can attract students' attention and help them learn the material faster.